Singlet Oxygen Generation Enhanced by Silver-Pectin Nanoparticles - de Melo, Luciana S. A.; Gomes, Anderson S. L.; Saska, Sybele [UNESP]; Nigoghossian, Karina [UNESP]; Messaddeq, Younes [UNESP]; Ribeiro, Sidney José Lima [UNESP]; de Araujo, Renato E. (Springer/plenum Publishers, 2012)
We demonstrate the potential application of silver-pectin nanoparticles on photodynamic therapy, on a solution-base platform. Photodynamic therapy is a medical technique which uses a combination of photosensitizing drugs and light to induce selective damage on the target tissue, by electronically excited and highly reactive singlet state of oxygen. Metal enhanced singlet oxygen generation in riboflavin water solution with silver-pectin nanoparticles was observed and quantified. Here 13 nm silver nanospheres enclosed by a pectin layer were synthesized and it interaction with riboflavin molecule was analyzed. Pectin, a complex carbohydrate found in plants primary cell walls, was used to increase the biocompatibility of the silver nanoparticles and to improve metal enhanced singlet oxygen generation (28.5 %) and metal-enhanced fluorescence (30.7 %) processes at room temperature. The singlet oxygen sensor fluorescent green reagent was used to quantify the enhancement of the riboflavin singlet oxygen production induced by the silver colloid. We report a 1.7-fold increase of riboflavin emission and a 1.8-fold enhancement of singlet oxygen production.
Keywords: Metal nanoparticles; Photodynamic therapy; Plasmonics; Photosensitizer